Dynamic Regulation of the Nexus Between Stress Granules, Roquin, and Regnase-1 Underlies the Molecular Pathogenesis of Warfare Vesicants - Srivastava, Ritesh Kumar; Mishra, Bharat; Muzaffar, Suhail; Gorbatyuk, Marina S.; Agarwal, Anupam; Mukhtar, M. Shahid; Athar, Mohammad (Frontiers in Immunology, 2022)
The use of chemical warfare agents is prohibited but they have been used in recent Middle Eastern conflicts. Their accidental exposure (e.g. arsenical lewisite) is also known and causes extensive painful cutaneous injury. However, their molecular pathogenesis is not understood. Here, we demonstrate that a nexus of stress granules (SGs), integrated stress, and RNA binding proteins (RBPs) Roquin and Reganse-1 play a key role. Lewisite and its prototype phenylarsine oxide (PAO) induce SG assembly in skin keratinocytes soon after exposure, which associate with various RBPs and translation-related proteins. SG disassembly was detected several hours after exposure. The dynamics of SG assembly-disassembly associates with the chemical insult and cell damage. Enhanced Roquin and Regnase-1 expression occurs when Roquin was recruited to SGs and Regnase-1 to the ribosome while in the disassembling SGs their expression is decreased with consequent induction of inflammatory mediators. SG-targeted protein translational control is regulated by the phosphorylation-dependent activation of eukaryotic initiation factors 2α (eIF2α). Treatment with integrated stress response inhibitor (ISRIB), which blocks eIF2α phosphorylation, impacted SG assembly dynamics. Topical application of ISRIB attenuated the inflammation and tissue disruption in PAO-challenged mice. Thus, the dynamic regulation of these pathways provides underpinning to cutaneous injury and identify translational therapeutic approach for these and similar debilitating chemicals.